Vitamin D status of females in an elite gymnastics program - Lovell, G. (Clinical Journal of Sport Medicine, 2008)
Objective: Vitamin D plays an important role in calcium and bone metabolism. In Australia it has been assumed that all young athletes have good vitamin D levels. A survey of females in an elite gymnastics program was undertaken to determine their vitamin D and dietary calcium status.